Precollagen Type III N-terminal Propeptide (PIIINP) a Biomarker Onset in Hypertensive Patients - Mohammed, Hasanain Fadhil; Jaber, Sarah Hassan; al-Zubaidi , Ali Jabbar (Medical Science Journal for Advance Research, 2020)
The aim of this study is to asses PIIINP, lipid profile and BMI serum levels in patients with hypertension. The current research The results were Get it from the Draw Blood unity in Al-Sadder infirmary Teaching , Al-Najaf, Iraq, And AL HAKEEM General infirmary in AL-Najaf, Iraq, in 10 Dec 2018 – 19 Jan 2019. Age of hypertensive patients from 40 to Age 70 Normal blood pressure 40 to 70 years. The score show, serious increase (p<0.05) in PIIINP compared with control groups in patients with hypertension. For female patients, the findings of the reported substantially increased (p<0.05) for PIIINP relative to male patient groups. The findings showed a substantial increase (p<0.05) in PIIINP in age (60-70) relative to age (50-59) and (40-49) and increased substantially (p<0.05) in PIIINP in age (50-59) relative to age (40-49); The results showed significant differences in BMI between the hypertensive and the normotensive